EFFORTS TO INCREASE STUDENTS PASSING TECHNIQUES FOR FOOTBALL GAMES THROUGH DRILL AND PRACTICE METHODS - Isro' Riskiyanto; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
One of the most basic techniques in the game of soccer is to be able to make good and correct passes. This study aims to determine whether the drill and practice method can improve the ability of students at SDN Kamal 3 and the extent of the resulting improvement. This research is classified as a classroom action research method. The data collection techniques used in this research are interviews, observation, tests, and documentation. Based on the results of the research conducted at SDN Kamal 3, the researchers found that many students still could not do good and correct passing events. This research was held in 2 cycles. The results showed that in cycle 1, students experienced an increase from before, but the result was that there were still some students who had not yet completed the percentage of completeness which was at 69% and incompleteness was at 31%. In cycle 2, the drastic increase experienced by students with completeness is at a maximum of 100% while incompleteness is at a minimum of 0%. Based on these results, it can be concluded that the drill and practice method can improve students' abilities in carrying out passing techniques